2018
DOI: 10.1007/s11739-018-1816-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of electronic signout for ED-to-inpatient admission at a non-teaching hospital

Abstract: Admission handoff is a high-risk component of patient care. Previous studies have shown that a standardized physician electronic signout ("eSignout") may improve ED-to-inpatient handoff safety and efficiency in teaching hospitals. This model has not yet been studied in non-teaching hospitals. The objectives of the study were to determine the efficiency of an eSignout platform at a community affiliate hospital by comparing ED length of stay (LOS) for a 5-month period before and after implementation and to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Ryan et al 22 also reported a reduced median length of stay from 5 to 4 days ( p = 0.047). Singleton et al 24 and Chen et al 17 however showed no statistically significant change in length of stay following implementation of e-handovers.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Ryan et al 22 also reported a reduced median length of stay from 5 to 4 days ( p = 0.047). Singleton et al 24 and Chen et al 17 however showed no statistically significant change in length of stay following implementation of e-handovers.…”
Section: Resultsmentioning
confidence: 95%
“…Nazar et al 19 failed to clearly describe their aims for their study and also lost 69 per cent of their participants to follow up, well over the 20 per cent threshold for high bias. Singleton et al 24 failed to utilise a large enough sample size to provide confidence in the findings. All studies provided a clear description of their e-handover and used the same e-handover format throughout their individual study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations